A new species of Drepatelodes (Lepidoptera: Bombycoidea: Apatelodidae) from Floresta Nacional do Tapajós, Pará, Brazil - Elton ORLANDIN; Mônica PIOVESAN; Eduardo CARNEIRO (Acta Amazonica, 2025)
ABSTRACT Drepatelodes (Lepidoptera: Bombycoidea: Apatelodidae) is a genus of moths with very similar species, most of them described from the Amazon region, mainly from the Guiana Shield. Recent field samplings in the Floresta Nacional (FLONA) do Tapajós (Pará, Brazil) revealed the existence of a new species of Drepatelodes, described based on morphological characters. Drepatelodes cabana Orlandin, Piovesan & Carneiro sp. nov. presents wing morphology (structure and coloration) similar to Drepatelodes quadrilineata (Schaus, 1921), Drepatelodes decaensi Herbin, [2024] and Drepatelodes parallela Herbin, [2024] but can be differentiated from them by characters found in the male genitalia: sacculus with a spiniform process, located approximately 2/3 of the valvae length (process located at the base of the valvae in D. parallela), uncus without a pair of socii (present in D. quadrilineata and D. decaensi), aedeagus straight (L-shaped in D. quadrilineata and D. decaensi) and vesica with cornutus (absent in D. quadrilineata, D. parallela and with five cornuti in D. decaensi). The new species was recorded from FLONA do Tapajós and northern Mato Grosso, Brazil. With the description of the new species, Drepatelodes now includes 13 species, nine of which are described from the Amazon region, although only three in the Brazilian Amazon. Therefore, collections in other regions of the Amazon are necessary to expand the distribution of known species or even discover new species for the genus.